Overall equipment effectiveness as a metric for assessing operational losses in wind farms: a critical review of literature - Sathler, Kelvin Palhares Bastos; Salonitis, Konstantinos; Kolios, Athanasios (Taylor & Francis, 2023)
To become more competitive, less dependent on financial support and more attractive for investors, wind energy needs to reduce its final cost of energy. According to Levelized Cost of Energy, there are two ways to achieve this goal, by reducing costs or increasing production. Overall Equipment Effectiveness (OEE) is a widely used metric in manufacturing systems, supporting operators to enhance productivity by reducing operational losses. Therefore, this study aims to perform a qualitative literature review of the main operational losses following the OEE metric, namely availability, performance and quality, adjusting it to wind energy systems. Introduction of this metric can be a valuable tool towards an integrated indicator linking production and losses, allowing comparison between assets deployed in different settings.
Keywords: overall equipment effectiveness; wind energy; availability; performance